Impacts of Company Size, Company Age, and the Generation of the Leader on Firm Performance - Daniel Kurniawan; Elia Ardyan; Istiatin; Luhgiatno (Binus Business Review, 2022)
The impact of family business has been recognized globally. However, according to some facts and previous studies, the performance of family businesses may decline as they age and the generations change. The research tried to explore the differences in firm performances based on company size, company age, and the generation of the leaders of the firms to confirm the results from the previous study. The data were compiled from 213 companies that vary in size. There were micro, small, small-medium, big-medium, and big firms. The possible presence of significant differences in firm performance based on company size, age, and generation of the leaders was analyzed using the Analysis of Variances (ANOVA). ANOVA test shows no significant differences in company age, company size, and the generation of the leaders toward their firm performances. The research clarifies the previous studies stating that there are significant differences in those three independent variables toward firm performance. The research also shows no significant difference in different generation of the leaders toward company size. Hence, it means the firm performance of companies cannot be determined only by knowing its size, age, or the generation of the leaders. There must be other factors that can help to identify the firm performance of a company.